Unveiling Insights: Students' Knowledge and Mastery of Microscopes at SMAN 1 Rasau - Eria Fitriani; Wolly Candramila; Asriah Nurdini Mardiyyaningsih (Postgraduate, University of Mataram, 2025)
The utilization of the biology laboratory at SMA Negeri 1 Rasau has not been optimal, particularly in microscope practice, which plays a crucial role in developing students’ observational skills. This study aims to explore students’ knowledge of microscopes and their usage, with the goal of informing improvements in instructional strategies and laboratory management. A descriptive qualitative method was employed, using a questionnaire focused on four main aspects: the name of the microscope, its function, its parts, and how to operate it. The findings showed that although all students were able to correctly identify the microscope's name, their understanding of its function, structure, and operational procedures remained limited. These results highlight the need to improve both conceptual and practical comprehension through experiential, hands-on learning approaches. It is recommended that schools increase the frequency of laboratory practice, provide more structured guidance, and adapt instruction to address the areas where students show the most misunderstanding.